Efforts to Reduce Maternal, Infant, and Under-Five Mortality in Semarang Regency - Endang Nur Widiyaningsih; Siti Zulaekah; Dhian Sukma Aprilliani; Syafiqa Rifda Seftyarini (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2025)
In 2019, the poverty rate in Semarang Regency declined to 7.04%, down from 7.29% in 2018. Nevertheless, the number of maternal, infant, and under-five deaths in the region increased in 2020 compared to the previous year. Despite numerous interventions that have been implemented, mortality rates among mothers, infants, and young children remain considerably high. This condition is primarily attributed to the inadequate number of healthcare professionals in proportion to the population that must be served across an extensive geographical area. In light of this analysis, the present community engagement initiative seeks to contribute constructively through the development of nutrition education media aimed at promoting nutritional awareness and preventing early maternal, infant, and child mortality. The educational media will be designed to be engaging and culturally appropriate, aligning with the characteristics of the local population in Semarang Regency. Furthermore, this initiative also aims to develop a variety of supplementary feeding (PMT) menus to serve as a reference for improving the nutritional intake of pregnant women and those experiencing Chronic Energy Deficiency (CED).